Students' digital literacy levels and their ability to analyse contemporary issues on social media among grade XII students at Tri Ratna West Jakarta - Widhi Widhi; Taridi Taridi; Burmansah Burmansah (Universitas Sebelas Maret, 2025)
The development of digital technology has changed the way students access and understand information. Digital literacy encompasses not only technical skills, but also critical thinking skills, media ethics, and information evaluation. However, there is still a gap between access to technology and critical understanding among users, especially in distinguishing valid information from hoaxes. Low levels of digital literacy contribute to the spread of disinformation, a lack of awareness of digital ethics, and low student engagement in analysing social issues. This study aims to analyse the influence of digital literacy on students' ability to understand and evaluate contemporary issues circulating on social media. The method used in this study was a survey with a quantitative approach, involving 43 Year 12 students from Tri Ratna High School in West Jakarta as respondents. Data analysis was performed using simple linear regression to measure the relationship between digital literacy levels and the ability to analyse issues. The results show that digital literacy has a positive and significant influence on the ability to analyse contemporary issues. The coefficient of determination (R²) of 92.8% indicates that digital literacy plays an important role in improving students' analytical skills regarding social media content. This study recommends the integration of digital literacy education into the school curriculum to strengthen students' analytical skills.